Refining evidence-based retinopathy of prematurity screening guidelines: The SCREENROP study. Issue 7 (12th August 2019) - Sabri, Kourosh; Shivananda, Sandesh; Farrokhyar, Forough; Selvitella, Alessandro; Easterbrook B Kin, Bethany; Seidlitz, Wendy; Lee, Shoo K; ,
Abstract: Purpose: Retinopathy of prematurity (ROP) is a potentially blinding condition affecting premature infants for which less than 10% of babies undergoing screening require treatment. This study assessed and validated predictors of developing clinically significant ROP (type 2 or worse) and ROP requiring treatment. Design: Nationwide retrospective cohort study. Methods: This study included infants born between January 2014 and June 2016, admitted to level 3 neonatal intensive care units across Canada who underwent ROP screening. Data were derived from the Canadian Neonatal Network database. Predefined ≥ 1% risk for clinically significant retinopathy or prematurity and ROP requiring treatment was set as threshold for screening. Thirty-two potential predictors were analyzed, to identify and validate the most important ones for predicting clinically significant ROP. The predictors were determined on a derivation cohort and tested on a validation cohort. Multivariable logistic regression modeling was used for analysis. Results: Using a sample of 4, 888 babies and analyzing 32 potential predictors, capturing babies with ≥1% risk of developing clinically significant ROP equated to screening babies with birth weight (BW) <1, 300 g or gestational age (GA) <30 weeks while capturing babies with ≥1% risk of requiring ROP treatment equated to screening babies with BW <1, 200 g or GA <29 weeks. Conclusions: The Canadian ROP screening criteria can be modified to screen babies with BW <1, 200 g or GA <30 weeks. Using these criteria, babies requiring treatment would be identified while reducing the number of babies screened unnecessarily.